The Utilization Of Information Technology On Performance Improvement At Bank Perkreditan Rakyat Banten Province - Lena Erdawati; Dian Esha; Siti Asriah Immawati (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
Purpose: This study aims to determine the effect of social factors, task suitability, long-term consequences, conditions that facilitate the use of information technology, and the complexity of the use of information technology in rural banks in Banten Province. Design/methodology/approach: The sampling technique uses a stratified random sampling technique, which is proportionally random sampling from each group in each BPR in Banten Province. Findings: The results of the research show that partially and simultaneously social factors, Affect, suitability of tasks, long-term consequences, conditions that facilitate the use of information technology, and complexity affect the utilization of information technology. And the utilization of information technology has a significant effect and has a very strong relationship to the performance of BPR in Banten Province Research limitations/implications: The target population in this study is BPR in Banten Province, while the affordable population is 15 BPRs in Banten Province, each of which is taken as many as 10 respondents. Practical implications: User perception in viewing information technology is getting better, this is marked by a system that is then deemed to provide benefits in helping companies internally and externally. Internal includes activities in business processes such as making invoices, travel documents and others. While external factors include the company's business strategy which is assisted by information technology to win from its competitors, including to bind customers. Paper type: Research paper